2008
DOI: 10.1152/ajpregu.00390.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mesolimbic dopamine neurons during novel and daily limited access to palatable food is blocked by the opioid antagonist LY255582

Abstract: Sahr AE, Sindelar DK, Alexander-Chacko JT, Eastwood BJ, Mitch CH, Statnick MA. Activation of mesolimbic dopamine neurons during novel and daily limited access to palatable food is blocked by the opioid antagonist LY255582. Am J Physiol Regul Integr Comp Physiol 295: R463-R471, 2008. First published June 4, 2008 doi:10.1152/ajpregu.00390.2007.-An analog of the trans-3,4-dimethyl-4-(3-hydroxyphenyl)piperidine series (LY255582) exhibits high in vitro binding affinity and antagonist potency for the -, ␦-, and -o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 59 publications
(73 reference statements)
4
27
0
1
Order By: Relevance
“…Current results suggest that consummatory rather than anticipatory aspects of feeding are associated with the activation of the mesolimbic pathway. This possibility agrees with previous microdialysis studies showing that Acb dopamine release mainly occurs during the consummatory phase of feeding and not during the anticipatory phase (Sahr et al, 2008;Wilson et al, 1995). Notably, an activation of the MAcbSh neurons was detected in anticipation to the fourth HFD consumption event, similarly as found for the IF dopamine neurons.…”
Section: Discussionsupporting
confidence: 92%
“…Current results suggest that consummatory rather than anticipatory aspects of feeding are associated with the activation of the mesolimbic pathway. This possibility agrees with previous microdialysis studies showing that Acb dopamine release mainly occurs during the consummatory phase of feeding and not during the anticipatory phase (Sahr et al, 2008;Wilson et al, 1995). Notably, an activation of the MAcbSh neurons was detected in anticipation to the fourth HFD consumption event, similarly as found for the IF dopamine neurons.…”
Section: Discussionsupporting
confidence: 92%
“…The first report showing that blockade of opioid receptors decreases food intake used naloxone, a general opioid receptor antagonist [5]. Since then, numerous studies have established that both systemic and intracerebroventricular administration of general opioid receptor antagonists reduces food intake and body weight in rodent models, including genetically obese Zucker and diet-induced obese rats [6,7,8,9,10]. Accordingly, agonists of the opioid receptors increase food intake [11].…”
Section: Opioid Receptors and Feeding Behavior: Homeostatic And Hedonmentioning
confidence: 99%
“…Similarly, another report found that rats fed on high-fat diet receiving a chronic oral treatment with LY255582 for 14 days reduced body fat by decreasing food intake and stimulating lipid utilization [9]. Furthermore, LY255582 also inhibited the consumption of a highly palatable diet after a 4-day treatment and blocked the activation of mesolimbic dopamine neurons in the nucleus accumbens induced by high palatable diet [10]. Thus, LY255582 appears to be a potent and long-acting anorectic drug.…”
Section: Opioid Receptors and Feeding Behavior: Homeostatic And Hedonmentioning
confidence: 99%
“…The reason for this is that these foods have the ability to activate the central neural circuits involved in the regulation of motivation and reward (the mesolimbic reward system) in a manner analogous to alcohol and drugs of abuse (20,21). Studies in both humans and animals have shown that the intake of fat and sugar produces acute increases in the synthesis and secretion of opioids and dopamine within the central reward system (22)(23)(24)(25)(26)(27). The similarity between the acute effects of palatable foods and those of well-characterized drugs of abuse has led to the concept that overexposure to palatable foods may also result in long-term alterations to reward pathway sensitivity.…”
Section: High-fat/high-sugar Junk Foods and The Mesolimbic Reward Systemmentioning
confidence: 99%